Penal Policy Against Online Gambling Criminals Reviewed from Law Number 19 of 2016 Concerning Electronic Information and Transactions - Firdaus, Aras; Lubis, Mohd. Ansor; Arkan, Daniyel; Kurniawan, M. Taufik (Civiliza Publishing, 2025)
Legal efforts from the government carried out by law enforcers for criminal acts of online gambling. The implementation of legal applications in society does not only depend on legal awareness in society, but is also greatly influenced by law enforcement officials. Current developments that encourage progress in the field of technology have a positive impact on society so that people can easily access various websites on electronic media. Developments in internet-based electronic media can also have negative impacts such as online gambling. Online gambling is a form of betting between fellow players who use money as a bet, so online gambling users can do this via electronic media connected to the internet. Online gambling is one of the unlawful acts carried out by adults and teenagers, but it also violates the values ​​and norms that exist in society. Therefore, legal efforts from the government against online gambling players are increasingly common in society due to developments in science and technology. One type of gambling that will be followed up is online slots. The government requires strict criminal action to be imposed on online gambling users. Criminal acts for online gambling perpetrators in Indonesia are regulated in Article 303, article 303 bis of the Criminal Code, article 2 paragraphs (1), (2), (3) of Law no. 7 of 1974 concerning Controlling Online Gambling and also article 27 paragraph 2 Jo. Article 45 paragraph 2 of the ITE Law.